Radical Pacifism, Limited Pacifism or Just War? (A Response to Professor Jacek Hołówka) - Adam Cebula (Studia Philosophiae Christianae)
This article formulates a critical response to Professor Jacek Hołówka’s opinion on (the philosophical debate about) the morality of war. It is claimed that by rejecting the plausibility of any argument justifying the occasional permissibility of military action. Hołówka finds it difficult to avoid (tacitly) endorsing some form of pacifism. In its radical version – presumably most closely matching Hołówka’s apparent position on war ethics – pacifism is shown to be completely unsupported by any serious social or political theory. More extensive analysis is focused on a compromise version of pacifism proposed recently by David Rodin. Described as “the middle ground between pacifism and just war theory,” Rodin’s proposal permits military resistance to genocidal violence while banning all other types of war, specifically defensive wars waged by invaded states. As closer scrutiny indicates, the view is based on faulty analogies, it disregards the reasonably expected increase in human rights abuses following most invasions, and it underestimates the natural inclinations of some aggressor states to embrace murderous methods of subjugating the populations of the annexed territories. What is more, the limited pacifism Rodin promotes is bound to effectively incapacitate sovereign states even when they confront unquestionably genocidal aggression (in most cases preceded by a purely political “takeover” of the attacked country). This paper concludes by endorsing the states’ traditional right to self-defence: granted only to “minimally just societies,” it turns out to be the most credible safeguard against conventional military aggression and its possible calamitous escalations – the threat of the latter being all too often grossly underrated by pacifists.